Post-tensioned concrete bridges Anglo-French liaison report = Ponts en beton precontrait par post-tension : Rapport conjoint franco-britannique sur l'etat de l'art (Thomas Telford, 1999)
In 1994, the UK and French central government highway agencies set up a joint venture to liaise on issues of construction repair and management of post-tensioned concrete bridges. This book provides a record of this co-operation.